Gender dan Masa Kerja sebagai Variabel Moderator dalam Hubungan Work Life Balance dan Kinerja Karyawan - Kusuma, Safira Nadya; Ezer Nainggolan , Eben Ezer; Muslikah , Etik Darul (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to identify the relationship between employee performance and work-life balance with gender and tenure as moderator variables. This study involved 384 employees working in Surabaya City. This study used a quantitative correlational approach. To find out how each variable contributes to the variability of employee performance, data analysis was carried out using a hierarchical regression analysis test. The results showed that there was a positive and significant relationship between work-life balance and employee performance (R² <0.092, and F Change <38.902). The addition of gender and tenure as moderator variables did not have a significant effect on the relationship. The second to fourth models showed significance values ​​above 0.05, indicating that the interaction between work-life balance and gender and tenure was not strong enough to significantly improve the model.